不同温度及二氧化碳浓度下培养的龙须菜光合生理特性对阳光紫外辐射的响应 - 杨雨玲; 李伟; 陈伟洲; 徐军田 (2013)
为了研究不同温度及CO2浓度下培养的大型海藻对紫外辐射的生理学响应,选取龙须菜(grACIlArIA lEMAnEIfOrMIS)作为实验材料。实验设置两个温度梯度(20℃和24℃),两种CO2浓度(390μl/l和1000μl/l)以及3种辐射处理,即可见光(PAr)处理(滤除紫外线A(uV-A)、紫外线b(uV-b),400—700 nM)、可见光加紫外线A(PA)处理(滤除uV-b,320—700nM)、PAb处理(全波长辐射280—700 nM)。结果表明,酸化、升温以及紫外辐射处理都未影响大型经济红藻龙须菜的叶绿素A和类胡萝卜素的含量。然而紫外辐射处理显著降低了龙须菜的有效光化学效率,其抑制水平在酸化处理的藻体中更为显著,并且随着温度的上升而进一步加剧;酸化与温度耦合使藻体对紫外辐射的敏感性增加,导致其较低的修复速率以及较高的损伤速率。 The marine red macroalga Gracilaria lemaneiformis( Bory) Weber-van Bosse( Gigartinales,Rhodophyta) is an economically important species for cultivation in China.The cultivation of this species has been extensively spread which could be found in both northern and southern parts of China.This species could support as food resources for both human beings and aquaculture,and could also be commonly used in agar industry and biofuel production.The growth condition of G.lemaneiformis in natural environment varied frequently( especially the temperature,light intensity and quality,pCO2),which would potentially affect the physiology and photosynthetic production.Though the physiological and ecological effects induced by these environmental variations have been extensively concerned and studied,multi-factor coupling effects to marine macroalgae are still less documented up to now.To study the physiological responses of G.lemaneiformis to multiple stressors of ocean acidification,rising temperature and Ultraviolet( UV) radiation,the thalli of G.lemaneiformis cultured under different temperature( 20 ℃ as control,and high temperature group where it was increased by 4 ℃ to 24 ℃) and different CO2concentrations( ambient atmosphere CO2concentration,390 μL / L,and elevated CO2concentration set at1000 μL / L which expected attain in the end of this century according to IPCC report of A1F1 scenario) for two weeks,and then the algae were treated with three levels of radiations( Photosynthetically active radiation,PAR,400—700 nm;Photosynthetically active radiation+Ultraviolet A,PA,320—700 nm; Photosynthetically active radiation +Ultraviolet A +Ultraviolet B,PAB,280—700 nm) respectively,in the short-period.The photosynthetic pigments and chlorophyll fluorescene characteristics of the thalli of G.lemaneiformis were determined.The results showed that ocean acidification,rising temperature and UV irradiance alone did not affect the concentrations of chlorophyll a and carotenoid of G.lemaneiformis,and also no interactive effects were found among the treatments.Elevated CO2in culture generally did not have a significant effect on the value of maximum relative electron transport rates( rETR max).Temperature had no effect on the photosynthetic light-use efficiencies for thalli of G.lemaneiformis.However,exposure to UV radiation strong reduced the values of light-use efficiencies.Moreover,exposure of UV radiation significantly lowered the effective quantum yield in both G.lemaneiformis thalli grown 20 and 24 ℃,with the inhibition rate being more pronounced in the algae grown under high CO2condition together with increased temperature than the algae grown at control conditions( ambient CO2concentration and 20 ℃).Combine effects of ocean acidification and rising temperature enhanced the sensitivity of G.lemaneiformis to UV radiation,which could be reflected by the increased damage rate( k),decreased repair rate( r),and finally decreased ratio of repair to damage( r / k) in the thalli grown at high CO2concentration together with increased temperature.Taken together,we proposed that under the background of global change,intensified UV radiation( ozone hole continue exist),increased surface seawater temperature and enhanced ocean CO2absorption( ocean acidification) will synergistically exert negative effects on photosynthetic performance of G.lemaneiformis,and could thereby potentially decrease the yield and affect the aquaculture of this species. 国家海洋863项目(2012AA10A411); 国家自然科学基金(41106093); 科技部农业科技成果转化资金项目(2012GB2E000340)